Chemoselective Electrochemical Hydrogenation of Ketones and Aldehydes with a Well‐Defined Base‐Metal Catalyst. Issue 62 (4th October 2020) - Fokin, Igor; Siewert, Inke
Abstract: Hydrogenation reactions are fundamental functional group transformations in chemical synthesis. Here, we introduce an electrochemical method for the hydrogenation of ketones and aldehydes by in situ formation of a Mn‐H species. We utilise protons and electric current as surrogate for H2 and a base‐metal complex to form selectively the alcohols. The method is chemoselective for the hydrogenation of C=O bonds over C=C bonds. Mechanistic studies revealed initial 3 e − reduction of the catalyst forming the steady state species [Mn2 (H−1 L)(CO)6 ] − . Subsequently, we assume protonation, reduction and internal proton shift forming the hydride species. Finally, the transfer of the hydride and a proton to the ketone yields the alcohol and the steady state species is regenerated via reduction. The interplay of two manganese centres and the internal proton relay represent the key features for ketone and aldehyde reduction as the respective mononuclear complex and the complex without the proton relay are barely active. Abstract : An electrochemical protocol is herein presented for the hydrogenation of ketones forming selectively the corresponding alcohols using protons and electric current. A dinuclear manganese catalyst is used with an internal proton relay to facilitate the reaction. Investigation by means of electrochemical methods and IR spectroelectrochemistry shed light on the catalytic cycle.